Program „nowej” estetyki wobec oczekiwań archeologów - Minta-Tworzowska, Danuta (Folia Praehistorica Posnaniensia, 2019)
The article is devoted to considerations regarding the idea of „new aesthetics” and its importance for archeology, especially prehistoric archeology. The current scientific reality as exceeding current paradigms and expanding research fields is diagnosed. This process also applies to the borders of art, which until recently seemed to be established, fixed and guaranteeing its clear separation from other spheres of life. The article shows aesthetics as noting this process and subject to change. This complicated current situation has created the idea of „new aesthetics”, entering new areas that previously did not belong to art or aesthetics. Similarly, the methods of analyzing these phenomena do not have a predetermined status. This gives new opportunities, especially when you notice the manifestations of universal aesthetics. They also relate to prehistoric archeology, giving it the opportunity to participate in the discourse proposed by „new aesthetics.”